Evaluasi Sistem Anggaran Dana Bos Pada MTSN Bojonegoro II Kabupaten Bojonegoro - Sutrisno, Sutrisno; Hidayat, Widi; Muktiyanto, Ali (Journal of Accounting and Finance Management, 2024)
This study aims to evaluate the system in compiling and processing the BOS (School Operational Assistance) budget. The research method used is descriptive qualitative by describing and depicting. There are 2 sources of research to be used as information, namely Primary Data consisting of BOS treasury officials and Secondary Data consisting of BOS financial reporting. The techniques used for the study were interview techniques and observation techniques, resulting in research that the BOS fund budgeting system at MTsN Bojonegoro II through the Education Management Information System (EMIS) at www.emispendis.kemenag.go.id, BOS fund management in accordance with the MTsN Bojonegoro II Madrasah Activity and Budget Plan (RKAM) has covered all elements of the 8 National Education Standards, BOS fund budget reporting can be in the form of financial reporting including the General Cash Book, UP Cash Book